Estrés laboral y su influencia en el desempeño laboral de los asesores de negocios en la Caja Trujillo, Agencia España, 2012. - Romero Mego, Patricia Lisseth (2014)
The present investigation was made in order to determine the influence of job stress on job performance of business advisers Trujillo Box, agency Spain, 2012. Research was conducted descriptive level field with two variables , and the following methods : analytical method , deductive , inductive and statistical , and finally , data collection was done through quantitative ( survey ) , which consisted of nineteen items with three response alternatives , applied to 32 people ( census type ) . The results were presented in statistical tables absolute numbers and percentages , which provided different conclusions among which are : job stress in the business advisors of the Fund Trujillo, Spain Agency , is the result of work under pressure , and either by strict deadlines that must be met or achievement of goals , which can lead to low job performance. It was also determined that there is a negative correlation between the variables type, this means that higher job stress lower job performance. And although business advisors work stress symptoms have a good relationship with their customers.